Filipino Acronyms: How Filipinos Use Acronyms - Padate, Settie-Zhymah (International Journal of Language and Literary Studies, 2024)
Language is dynamic and is constantly changing. It also proves that language and technology are related. Because technology uses language. Social media sites have become communication platforms, that involve more language. One of the word formation processes that has become increasingly popular is the formation of acronyms. This study aimed to assess and analyze Filipino acronyms and classify them according to their use and how they are formed. The data were analyzed through document analysis. The acronyms reviewed in this study are listed and derived from YouTube videos. From the results of the study, it is found that in Filipino, acronyms are mostly used in science and technology and in social media sites that have sprung up due to technology, and acronyms were formed due to human needs. In this age of social media, whether young or old, these words need to be known and used to keep up with the modern era. People need to learn it to be able to understand the modern world they live in and to be able to continue to express themselves through language.